PSYCHOLOGICAL FACTORS OF STRESS RESISTANCE OF HIGHER EDUCATION STUDENTS IN WAR CONDITIONS (Psychology Travelogs, 2024)
The process of studying at a higher education institution, especially in the context of war, is not always unambiguous and smooth, and in any case, it affects the formation of a personality and the acquisition of various skills. The study aims to explore students' perceptions of stress, its scientific explanation depending on various factors, and to identify areas for its prevention and development of stress resistance. The study of the key issues is based on empirical data obtained during a survey (online questionnaire) of bachelor's and master's students (full-time, N=185). The data obtained were systematised, analysed and correlated with the available scientific knowledge, as well as with the results of observing the course of stress in students in the process of teaching at a pedagogical university. During the survey, the respondents - full-time students - were asked to assess the level of stress during the intersession period and during the session.Having examined the stressors that affect the process of full-time study in HEIs, we can conclude that they have a variety of determinants, many of which have their roots in the process of studying in secondary school. At the time of enrolment, young people are stressed after the Unified State Exam and are mostly unprepared for traditional forms of studying in higher education, unable to process information and find their own creative, extraordinary solutions to educational tasks, preferring to memorise in order to get a grade.
Keywords: stress; stress factors; stress resistance; higher education students; psychoprophylaxis